2017
DOI: 10.1038/srep45765
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Markov models reveal complexity in the diving behaviour of short-finned pilot whales

Abstract: Diving behaviour of short-finned pilot whales is often described by two states; deep foraging and shallow, non-foraging dives. However, this simple classification system ignores much of the variation that occurs during subsurface periods. We used multi-state hidden Markov models (HMM) to characterize states of diving behaviour and the transitions between states in short-finned pilot whales. We used three parameters (number of buzzes, maximum dive depth and duration) measured in 259 dives by digital acoustic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 57 publications
4
59
0
Order By: Relevance
“…The lack of a single foraging dive type is consistent with recent findings of Quick et al. () who described several dive types representing different levels of foraging effort in short‐finned pilot whales. Furthermore, social sounds and dive synchrony occurred in both foraging and non‐foraging contexts, indicating that social interactions occurred across the behavioral repertoire.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of a single foraging dive type is consistent with recent findings of Quick et al. () who described several dive types representing different levels of foraging effort in short‐finned pilot whales. Furthermore, social sounds and dive synchrony occurred in both foraging and non‐foraging contexts, indicating that social interactions occurred across the behavioral repertoire.…”
Section: Discussionsupporting
confidence: 91%
“…, Quick et al. ). Resting time often has both a physiologically enforced or “conserved” component (here, a recovery period required after a breath‐hold dive) and a “free” component that can be re‐allocated to other behaviors that, in turn, may be more conserved in the time budget (Dunbar et al.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the influence of these features on pilot whale foraging behavior, we used the 200 m isobath, generated from GEBCO bathymetric grids (30 arc-second resolution; www.gebco.net/data_and_products/ gridded _ bathymetry_data/), as a proxy for the location of the shelf break. Short-finned pilot whales typically forage at depths of 200−1000 m in our study area (Quick et al 2017), so consequently we identified canyons by examining valleys in the continental shelf slope that were evident in both the 200 m and 1000 m isobaths. We defined canyons as deep, steep-sided valleys that extended into the continental shelf for > 5 km in the cross-shelf direction of the 200 m isobath (Fig.…”
Section: Environmental Datamentioning
confidence: 99%
“…are deep-diving odontocetes that occur in shelf break regions and forage at depths of > 800 m (Baird et al 2002, Heide-Jør-gensen et al 2002, Garrison 2007, Aguilar Soto et al 2008, Jensen et al 2011, Baird 2016, Quick et al 2017. Information on the spatial habitat use of pilot whales in the northwest Atlantic is limited and, until recently, most information on their habitat use in this region was derived from shipboard and aerial surveys (although see Mate et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For these species, characterising flight modes may be more relevant than distinguishing between transit and resident movement, because of the implications on their energy budget. Such characterisation requires either the use of additional sensors, such as accelerometers, or the introduction of a third movement dimension (altitude), which is conceptually comparable to the use of depth when modelling diving behaviour of marine animals (Isojunno & Miller, ; Quick et al., ). Birds adopt different strategies to move through air, depending on their size, body structure, reasons for moving and environmental and weather conditions (Duerr et al., ; Hedenstrom, ; Lanzone et al., ).…”
Section: Introductionmentioning
confidence: 99%